1987
DOI: 10.1126/science.3563506
|View full text |Cite
|
Sign up to set email alerts
|

Ranking Possible Carcinogenic Hazards

Abstract: This review discusses reasons why animal cancer tests cannot be used to predict absolute human risks. Such tests, however, may be used to indicate that some chemicals might be of greater concern than others. Possible hazards to humans from a variety of rodent carcinogens are ranked by an index that relates the potency of each carcinogen in rodents to the exposure in humans. This ranking suggests that carcinogenic hazards from current levels of pesticide residues or water pollution are likely to be of minimal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
164
0
2

Year Published

1988
1988
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 547 publications
(168 citation statements)
references
References 114 publications
2
164
0
2
Order By: Relevance
“…Possible hazards from residues of synthetic chemicals should be routinely compared to the possible hazards from natural chemicals. We have found that when the same index is used for natural and synthetic chemicals, possible carcinogenic hazards from current levels of pesticide residues or water pollution are likely to be of minimal concern relative to the background levels of natural substances (117,118 …”
Section: Dna Repair and Other Inducible Defensesmentioning
confidence: 99%
“…Possible hazards from residues of synthetic chemicals should be routinely compared to the possible hazards from natural chemicals. We have found that when the same index is used for natural and synthetic chemicals, possible carcinogenic hazards from current levels of pesticide residues or water pollution are likely to be of minimal concern relative to the background levels of natural substances (117,118 …”
Section: Dna Repair and Other Inducible Defensesmentioning
confidence: 99%
“…As an example of this approach, Ames et al (1987) compared the potential carcinogenic hazard of selected naturally occurring and man-made chemicals in the environment using a human exposure dose/rodent potency dose (HERP) index that relates the potency of carcinogens in rodents to the exposure in humans (see Figure 10). These authors found that with regard to dietary exposures, a number of ''natural pesticides'' or ''natural toxic chemicals'' were present at higher concentrations in food and had similar or greater cancer potencies than some common man-made pesticides or chemicals.…”
Section: Comparisons To Background Levels Of Riskmentioning
confidence: 99%
“…Third, they can be used to illustrate how a particular indicator or biomarker of exposure is either appropriate or inappropriate for evaluating risks from a specific source, depending on whether measured exposure levels are distinguishable from background. All of these approaches provide additional information on the magnitude (and ultimately acceptability) of a particular chemical exposure or health risk or the usefulness of certain types of data.As an example of this approach, Ames et al (1987) compared the potential carcinogenic hazard of selected naturally occurring and man-made chemicals in the environment using a human exposure dose/rodent potency dose (HERP) index that relates the potency of carcinogens in rodents to the exposure in humans (see Figure 10). These authors found that with regard to dietary exposures, a number of ''natural pesticides'' or ''natural toxic chemicals'' were present at higher concentrations in food and had similar or greater cancer potencies than some common man-made pesticides or chemicals.…”
mentioning
confidence: 99%
“…As Ames et al recently pointed out, we need better measures of both risk and "anti-risk" factors for cancer. 37 Direct evidence of human cancer risk is derived from epidemiologic investigations and clinical observations. Table 4 shows six general approaches to delineating the environmental or occupational etiologies of human cancer, ranging from complex designs such as the cohort study or case control study, to simpler approaches, such as mathematical modelling and ecologic or correlational studies.…”
Section: Methods and Measures For Identifying Occupationalmentioning
confidence: 99%